Food quality management : Technological and managerial principles and practices - Luning, Pieternel, (Brill | Wageningen Academic, 2020)
Consumer understanding of food quality is crucial as their concerns for healthy, safe and sustainable food production remain high. This forces actors and stakeholders in the agribusiness and food industry to use quality management as a strategic approach in production and innovation. This book describes Food Quality Management (FQM) in one integrated concept. Firstly, all relevant aspects of food quality management are combined into one FQM-function model, which shaped the structure of the book chapters. Secondly, the authors have embedded the techno-managerial approach in the book. This approach starts with the notion that food quality is the outcome of the combined effect of food behaviour and human behaviour. The core principle of this approach is the concurrent use of technological and managerial theories and models to analyse food systems behaviour and people's quality behaviour and generate adequate improvements to the system. Topics covered in the book include food quality properties and concepts, essentials of quality management and food technology, and details about food and human behaviour. Furthermore, this book describes in detail the technological and managerial principles and practices in the five FQM functions, quality design, quality control, quality improvement, quality assurance, and quality policy and strategy. Moreover, for each function a special topic relevant for the function is highlighted, namely consumer-oriented design, product versus resource control, quality gurus and improvement, quality assurance standards and guidelines (like GMP, HACCP, ISO2200, IFS and BRC), and Total Quality Management. This publication is a must-have for students, researchers and agribusiness and food industry professionals active in various areas of food production in the supply chain. The integrated approach with technological and managerial principles and concepts for analysing food quality management issues makes this a valuable reference book.